Zipporah and Huldah - Erickson, Lois N.; Nang Chan Yeema (Hagerstown, Maryland, United States Review and Herald Publishing Association, 1989)
This is a 2-in-1 book depicting the stories of Zipporah and Huldah.
Keywords: Young Adult